Emerging Students’ Literary Experience and Reading Motivation through Shared Reading - Dianita, Filia; Hidayat, Ade; Ariani, Desti (LPPM Politeknik Raflesia, 2023)
The aim of this paper is to contribute to the role of shared reading in emerging students’ literary experience and their reading motivation. Shared reading replicates the bedtime story experience to the classroom reading activity. It provides enjoyment needed by the early readers. Sharing a big storybook to read along with friends and teacher can also give them a collaborative reading experience. Since the students are directed to read english text, shared reading offers opportunity in which the students start to learn how they read themselves. It is considered to enable them to enjoy and participate in the reading activity. Shared reading is thus as the strategy used in guiding and motivating students to read.